Performance of GDC with alkali metal carbonates as sintering aids - Nascimento, Rubens Maribondo do (2020)
Gd-doped ceria electrolytes (GDC, 10 at.% Gd) were prepared using a eutectic mixture of Li and Na carbonates as sintering aid (NLC - 0, 1, 3 and 5 mol%), using two processing routes (ceramic and chemical). Structural and microstructural characterization provided no evidence for significant solubility of alkali metal cations in GDC. Materials sintered at 1100 °C/4 h were similar in densification (> 95%) and microstructure to those obtained from a commercial powder sintered at 1500 °C/4 h. Impedance spectroscopy in air (200–600 °C) and as a function of oxygen partial pressure (from 0.21 to about 10−25 atm, 600–750 °C) showed that the low temperature conductivity of materials prepared using chemical synthesis surpassed the conductivity of a commercial GDC due to higher grain boundary conductivity. The estimated n-type conductivity of materials with NLC was also slightly higher than for pure GDC. The role of sintering aid and processing routes is discussed taking into consideration decomposition and volatilization of alkali salts